Optimización de los Parámetros de Producción del Biodiésel a Partir de Aceite Usado de las Pollerías - Terres León, Juan Carlos (2024)
In the present study, the optimum parameters for producing biodiesel by transesterification of used oil with methanol, using NaOH as a catalyst, were determined. The used oil was collected from poultry farms in the Pichari district. A three-level, four-factor Box-Benhken design with four replicates in the center and the response surface method were used to optimize the conditions of the trans-esterification process. The selected factors were the methanol-oil molar ratio (6, 9, and 12), NaOH concentration (0.5, 1.25, and 2.0), temperature (35, 45, and 55), and reaction time (30, 60, and 90). The selected response was the biodiesel yield. The optimum production conditions were: methanol-oil molar ratio; 9, NaOH concentration; 1.21%; temperature, 57 °C; and time, 62 min at a stirring frequency of 700 rpm. The estimated yield under these conditions was 94%. Three verification tests under these conditions showed a yield of 94.6%, indicating that the experimental yield is very close to the estimated yield, with a margin of error of 1.5%, considered acceptable. The biodiesel produced under these conditions meets the specifications of ASTM D6751 standards for flash point, water and sediment content, kinematic viscosity, acid number and sulfur content, making it an alternative fuel to diesel.